High-efficiency and stable short-delayed fluorescence emitters with hybrid long- and short-range charge-transfer excitations - Guoyun Meng; Hengyi Dai; Qi Wang; Jianping Zhou; Tianjiao Fan; Xuan Zeng; Xiang Wang; Yuewei Zhang; Dezhi Yang; Dongge Ma; Dongdong Zhang; Lian Duan (Nature Communications, 2023)
Abstract The pursuit of ideal short-delayed thermally activated delayed fluorescence (TADF) emitters is hampered by the mutual exclusion of a small singlet-triplet energy gap (ΔE ST) and a large oscillator strength (f). Here, by attaching an multiresonance-acceptor onto a sterically-uncrowded donor, we report TADF emitters bearing hybrid electronic excitations with a main donor-to-acceptor long-range (LR) and an auxiliary bridge-phenyl short-range (SR) charge-transfer characters, balancing a small ΔE ST and a large f. Moreover, the incorporation of dual equivalent multiresonance-acceptors is found to double the f value without affecting the ΔE ST. A large radiative decay rate over an order of magnitude higher than the intersystem crossing (ISC) rate, and a decent reverse ISC rate of >106 s−1 are simultaneously obtained in one emitter, leading to a short delayed-lifetime of ~0.88 μs. The corresponding organic light-emitting diode exhibits a record-high maximum external quantum efficiency of 40.4% with alleviated efficiency roll-off and extended lifetime.